"Corona Cooking": The interrelation between emotional response to the first lockdown during the COVID-19 pandemic and cooking attitudes and behaviour in Denmark. (March 2022) - Grunert, Klaus G.; Janssen, Meike; Nyland Christensen, Rikke; Teunissen, Lauranna; Cuykx, Isabelle; Decorte, Paulien; Reisch, Lucia A.
Highlights: We investigated how states of attitudes to food shopping and cooking changed during the COVID-19 lockdown in Denmark. People who changed attitude states were most likely to change towards more liking of food shopping and cooking. Attitude states were linked to food literacy and buying behaviour. People with stronger negative emotional reactions to the pandemic were more likely to change. Abstract: For this study, the authors measured attitudes toward shopping for food and cooking, before and during the first lockdown due to the COVID-19 pandemic, among a sample of 526 Danish consumers, using an online survey. To analyse changes due to the lockdown, they applied a latent class Markov model, which revealed four states: middle of the road, love cooking (and like shopping), like shopping and cooking, and do not like shopping or cooking. In estimating transition probabilities, the findings reveal that most respondents remained in the same state before and during the lockdown, but those that changed were more likely to exhibit relatively higher liking of shopping and cooking. These states also reflect variations in people's food literacy and self-reported food consumption. Finally, respondents with stronger negative emotional reactions to the lockdown were more likely to change their states.